[Ag(μ‐en)][ReO4]: An Intermediate during Preparation of the Ethylene Epoxidation Catalyst. Issue 23 (12th September 2022) - Badea, Désirée; Karpov, Andrey; Jansen, Martin; Bruns, Jörn
Abstract: Preparation of a catalyst for the ethylene oxide production requires impregnation of a porous corundum support with an aqueous silver ethylene diamine oxalate complex solution, to which among others NH4 [ReO4 ] is added. Here we report on [Ag(μ‐ en )][ReO4 ] that precipitates from such a mixture. Single crystal structure analysis has revealed a striking similarity of the [Ag(μ‐ en )] + entity with the same complex cation encountered in [Ag(μ‐ en )]2 (C2 O4 )×2H2 O. Silver is coordinated end‐on to the nitrogen atoms of the en ligands. The [ReO4 ] − anions are not bonded to the silver cations, but instead involved in N−H⋅⋅⋅O hydrogen bonds to the ethylene diamine molecules. The first step of thermal degradation occurs at approximately the same temperature for both, the main component precipitate [Ag(μ‐ en )]2 (C2 O4 )×2H2 O and [Ag(μ‐ en )][ReO4 ], warranting proximity of the rhenium promoter and the elemental silver deposit. At 300 °C, the temperature at which the catalyst for EO synthesis is commonly calcined, the decomposition product of plain [Ag(μ‐ en )][ReO4 ] under synthetic air is Ag[ReO4 ], in full analogy to industrial manufacturing process for selected Re‐promoted EO catalyst formulations. Abstract :